Daily consumption of cranberry improves endothelial function in healthy adults: a double blind randomized controlled trial. Issue 7 (24th March 2022) - Heiss, Christian; Istas, Geoffrey; Feliciano, Rodrigo P.; Weber, Timon; Wang, Brian; Favari, Claudia; Mena, Pedro; Del Rio, Daniele; Rodriguez-Mateos, Ana
Abstract : Previous studies indicate cardiovascular health benefits of cranberry juice consumption. Abstract : Background : Previous studies indicate cardiovascular health benefits of cranberry juice consumption. However, whether daily consumption of whole cranberries will have sustained vascular benefits in healthy individuals is currently unknown. Objective : To investigate the vascular effects of acute and daily consumption of freeze dried whole cranberry in healthy men and how effects relate to circulating cranberry (poly)phenol metabolites. Methods : A double-blind, parallel-group, randomized controlled trial was conducted in 45 healthy male adults randomly allocated to 1 month daily consumption of either cranberry (9 g powder solubilized in water equivalent to 100 g of fresh cranberries, 525 mg total (poly)phenols) or control (9 g powder, no (poly)phenols). Flow-mediated dilation (FMD, primary outcome), pulse wave velocity (PWV), aortic augmentation index (AIx), blood pressure, heart rate, blood lipids, and blood glucose were assessed at baseline and at 2 h on day 1 and after 1 month. Plasma and 24 h-urine were analyzed before and after treatment using targeted quantitative LC-MS methods including 137 (poly)phenol metabolites. Results : Cranberry consumption significantly increased FMD at 2 h and 1-month (1.1% (95% CI: 1.1%, 1.8%); p treatment ≤ 0.001; p treatment × time = 0.606) but not PWV, AIx, blood pressure, heart rate, blood lipids, and glucose. Of the 56 and 74 (poly)phenol metabolites quantified in plasma and urine, 13 plasma and 13 urinary metabolites significantly increased 2 h post-consumption and on day 1, respectively, while 4 plasma and 13 urinary metabolites were significantly higher after 1-month of cranberry consumption, in comparison with control. A multi-variable stepwise linear regression analysis showed that plasma cinnamic acid-4′-glucuronide, 4-hydroxybenzoic acid-3-sulfate, 2, 5-dihydroxybenzoic acid, 3′-hydroxycinnamic acid, and 5- O -caffeoylquinic acid were significant independent predictors of 2 h FMD effects ( R 2 = 0.71), while 3′-hydroxycinnamic acid, 4-methoxycinnamic acid-3′-glucuronide, 3-(4′-methoxyphenyl)propanoic acid 3′-sulfate, and 3-(4′-methoxyphenyl)propanoic acid 3′-glucuronide predicted the 1-month FMD effects ( R 2 = 0.52). Conclusions : Acute and daily consumption of whole cranberry powder for 1 month improves vascular function in healthy men and this is linked with specific metabolite profiles in plasma. The National Institutes of Health (NIH)-randomized trial records held on the NIH ClinicalTrials.gov website (NCT02764749). ; https://clinicaltrials.gov/ct2/show/NCT02764749